And they returned : life in Leyte during World War II - Castillo, Evelyn Chapman (Houston, Texas : Bright Sky Press, 2015)
"A personal understanding of the WWII Japanese invasion and occupation of the Philippines. Hipolita Chapman, the author's mother, married at age twelve, was widowed, and faced the 1941 invasion of Leyte alone, taking her family into hiding in the mountains before being forced to live under Japanese occupation"-- Provided by publisher.
Keywords: World War, 1939-1945 -- Philippines -- Personal narratives